Digital oriented human resource management in strengthening maritime industry competitiveness - Retno Anggoro; Endra Winarni; Khaeroman Khaeroman (Business, Accounting, and Knowledge Journal, 2026)
The maritime industry plays a strategic role in supporting national economic growth; however, its performance is highly dependent on the quality and effectiveness of human resource management. This study aims to examine the role of competency-based human resource management in improving organizational performance within the maritime industry. Specifically, the research analyzes how employee competencies, training programs, and performance-based evaluation systems contribute to workforce productivity and organizational effectiveness. This study employs a quantitative research approach using survey data collected from employees working in maritime-related organizations, including shipping services, port operations, and maritime education institutions. Data were analyzed using multiple regression analysis to test the proposed relationships between competency-based human resource management practices and organizational performance indicators. The findings indicate that competency development, structured training, and transparent performance appraisal systems have a positive and significant effect on employee performance, which in turn enhances overall organizational performance in the maritime sector. These results highlight the importance of aligning human resource strategies with industry-specific competency standards to strengthen competitiveness and sustainability. This study contributes to the human resource management literature by providing empirical evidence from the maritime context, which remains underexplored in prior studies. Practically, the findings offer insights for maritime industry managers and policymakers to design effective human resource strategies that support workforce development and long-term organizational performance.